Pendekatan Teori Pendidikan Anak Antara Ibnu Sina dan Jean Piaget: Pendekatan Kognitif dan Holistik - Tisna, Mohamad (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2025)
The approach to children's education is an important foundation in building a generation with character, adaptive, and intelligent. Ibn Sina and Jean Piaget offer two significant theories, with different but complementary approaches. Ibn Sina emphasizes holistic education that includes intellectual, emotional, physical, and spiritual dimensions, while Jean Piaget focuses on cognitive development through structured stages. This study aims to analyze and compare the theoretical approaches to children's education from these two figures, especially in the context of cognitive and holistic approaches. The research method used is a literature study by analyzing relevant articles, books, and research reports published in the last five years. The results of the study show that Piaget's theory is very relevant to understand children's intellectual development through systematic stages, while Ibn Sina's approach complements by integrating moral and spiritual values. The combination of these two theories offers the potential to create a more comprehensive and adaptive education system, in accordance with the needs of modern education. Education based on Ibn Sina's holistic values and Piaget's cognitive structure can be used to build a balanced curriculum, improve intellectual abilities while shaping students' character.